Epidemiology of infant burn in Eastern Saudi Arabia - Alsalman, Abdulla K. (Saudi Med J, 2015)
OBJECTIVES: To identify the epidemiology, pattern, outcome, and impact of infant burns in Eastern Saudi Arabia. METHODS: We conducted a retrospective review of admitted infants charts over 4 years (2008-2013) at the Burn Unit of King Fahad Hospital, Hofuf, Al-Ahsa, Saudi Arabia. The charts were reviewed for age, gender, etiology, site of injury, total body surface area (TBSA), depth of burn, hospital stay, and discharge status. RESULTS: The total number of admissions to the Burn Unit was 510 cases. Out of these cases, 84 were infants, constituting 16.5% of total admissions. Scald burn was the most common etiology affecting 73 infants (86.9%). The highest percentage of total body surface area was between 5-10%, which occurred in 41 infants (48.8%). The average hospital stay was 10 days. No infant mortality was reported during this period. CONCLUSION: The prevalence of burns among infants in our hospital is high, and preventive measures must be implemented to decrease the occurrence of burns in this age group.